Decomposing the Labor Productivity Gap between Upper-Middle-Income and High-Income Countries - Amin, Mohammad (World Bank E-Library Archive, 2019)
Using firm-level survey data on registered private firms collected by the World Bank's Enterprise Surveys, this paper compares the level of labor productivity in 22 upper-middle-income countries and 11 high-income countries for which comparable data are available. The results show that labor productivity in the upper-middle-income countries is about 57.5 percent lower than in the high-income countries. The productivity difference is robust and holds for firms of different sizes and industries. The analysis uses the Oaxaca-Blinder decomposition to identify the sources of the productivity gap. It finds that the endowment effect and the structural effect contribute roughly equally to the productivity gap. Several firm- and country-level variables determine the productivity gap. The biggest contributors via the endowment effect include tertiary education attainment, law and order, and quality management proxied by international quality certification. Factors that contribute most via the structural effect include market size, secondary education attainment, and law and order. Thus, the results underline the importance of human capital, institutions, and market size for closing the productivity gap between the upper-middle-income and high-income countries